Some Theories of Educational Marketing - . Hasbi (International Conference on Education and Language (ICEL), 2014)
Marketing is a method to provide the best service and product for the customers for the sake of producers long benefit and existence. Educational institutions as a service provider for customers should be aware of the marketing theories and techniques so that they can give better service and higher quality of education. There are some products offered by educational institutions, however due to lack of awareness of the importance of marketing, some instituions not pay so much attention on its developments. This paper presents some theories of marketing for educational institutions. It is aimed at long term improvements in educational institutions.